TİP 2 DİABETES MELLİTUSLU HASTALARIN HASTALIKLARINI KABULLENME VE KENDİ BAKIMLARINDAKİ ÖZ YETERLİLİK DÜZEYLERİNİN BELİRLENMESİ - ŞİRECİ, EMİNE (Fırat Üniveristesi, 2012)
Bu araştırma tip 2 diyabetli hastaların hastalıklarını kabullenme ve öz yeterlilik düzeyleri ile etkileyen faktörleri belirlemek ve hastalığı kabul ile öz yeterlilik arasındaki ilişkiyi incelemek amacıyla tanımlayıcı olarak yapılmıştır.Araştırmaya Fırat Üniversitesi Hastanesi Endokrin Polikliniğine başvuran 156 tip 2 diyabet hastası alınmıştır. Veriler tanıtıcı özellikler ve hastalık ile ilgili değişkenlerin yer aldığı soru formu, öz yeterlilik ölçeği ve hastalığı kabul ölçeğiyle toplanmıştır.Çalışma sonuçlarının istatistiksel analizleri SPSS 15 programı kullanılarak yapılmıştır. İstatistik analizlerinde; yüzdelik, aritmetik ortalama, standart sapmaları, t-testi, Mann-Whitney U testi, Anova, Kruskal Wallis testi ve Bonferronili Mann-Whitney U testi kullanılmıştır.Hastaların ölçeklerden aldıkları ortalama puanlar incelendiğinde; hastalığı kabul ölçeğinden aldıkları puanın (27.82±5.70) yüksek olduğu saptanmıştır. Hastaların öz yeterlilik ölçeğinden aldığı puanlar incelendiğinde; toplam öz yeterlilik puanın (51.74±10.66) yüksek olduğu ve öz yeterlilik ölçeği alt boyutlarından özel beslenme ve kilo ortalama puanının 14.17±3.53, fiziksel egzersiz ortalama puanın 9.94±2.54, kan şekeri ortalama puanın 7.43±2.12 ve genel beslenme ve tıbbi tedavi kontrolü ortalama puanın 20.20±4.47 olduğu tespit edilmiştir.Hastaların cinsiyet, öğrenim durumu, meslek ve çalışma durumu, hastalık süresi, tedavi süresi, hastalığa ait bilgi alma durumuna göre hastalığı kabul ölçeğinden alınan ortalama puanların istatistiksel olarak anlamlı farklılık gösterdiği tespit edilmiştir (p<0.05).

This research has been conducted to determine the type 2 diabetic patients acceptance of the ıllness and the levels of self- efficacy and the factors affecting it and also look into the relation between the acceptance of ıllness and self-efficacyThis research includes 156 type 2 diabetes patients who applied to Fırat University Hospital Endocrine Polyclinic.Data were collected on demographics and disease variables in the form of the question, self-efficacy scale and the acceptance of ıllness scale.Operating results of the statistical analysis was performed by using SPSS 15 program. In statistical analysis was used percentage, arithmetic mean, standard deviation, t-test, Mann-Whitney U-test, ANOVA, Kruskal-Wallis test and Bonferronili Mann-Whitney U test.When the average scale scores of the patients examined, their acceptance of ıllness scale score (27.82 ± 5.70) was found high. When the scores of the patients from self-efficacy scale, it was found to be the total self-efficacy scores (51.74 ± 10.66) was high and the lower dimensions of self-efficacy scale, the average score of a special diet and weight 14.17 ± 3: 53, the average score of physical exercise 9.94 ± 2.54, the average score of blood glucose 7.43 ± 2.12 the average score of control point at general nutrition and medical treatment 20.20. ± 4.47.Patients were observed showed statistically significant differences gender, education level, occupation and employment status, disease duration, duration of treatment, the disease to receive information, according to the state acceptance of ıllness the scale from the average scores (p <0.05).It has been identified that patients age, method of treatment and the frequency control of diabetes statistically have affected the self-efficacy scale from average scores (p <0.05).It has been revealed that there is no statistically significant relation between patients the acceptance of illness scale average scores and the self-efficacy scale subscale average scores and average total scores (p> 0.05).Key Words: Type II Diabetes Mellitus, Acceptance of Illness, Self-efficacy.
Diabetes mellitus type ii patients? acceptance of their illness and determination of self efficacy levels for their own care
Keywords: Hemşirelik